Pendampingan Bahasa Perancis Pariwisata Bagi Pemandu Wisata di Kabupaten Pangandaran â€“ Jawa Barat - Racmadhany, Ariessa; Darmawangsa, Dante; Sopiawati, Iis; Sunendar, Dadang; Mulyadi, Yadi (Universitas Islam Nahdlatul Ulama Jepara, 2022)
This French language training is based on the limited ability of foreign languages other than English, namely French for tour guides in Pangandaran Regency. Until now there has been no formal education institution that provides French language in Pangandaran Regency, even though this area is an important tourist destination for West Java which is visited by many french tourists in 2019 (see Nurroni, 2019). Meanwhile, according to BAPPEDA West Java Provincial Government, this regency will become an international class tourist destination in 2021-2025. Departing from this goal, this service program provides training in French Tourism which can provide insight into french language skill to tour guides in Pangandaran Regency so that it will lead to improving the quality of their languages. This service aims to 1) provide French Tourism training for tour guides in Pangandaran Regency; 2) conduct a simulation of the jeux de rÃ´les-actes de parole technique (role play-technical speaking acts) based on local wisdom of Pangandaran Regency. Based on the results of the training, tour guides in Pangandaran Regency are familiar with the French alphabet and numbers, are able to carry out simple conversations, and introduce tourist objects in Pangandaran in a simple manner